2009
DOI: 10.2337/dc09-0536
|View full text |Cite
|
Sign up to set email alerts
|

Foot Muscle Energy Reserves in Diabetic Patients Without and With Clinical Peripheral Neuropathy

Abstract: OBJECTIVETo investigate changes in the foot muscle energy reserves in diabetic non-neuropathic and neuropathic patients.RESEARCH DESIGN AND METHODSWe measured the phosphocreatinine (PCr)/inorganic phosphate (Pi) ratio, total 31P concentration, and the lipid/water ratio in the muscles in the metatarsal head region using MRI spectroscopy in healthy control subjects and non-neuropathic and neuropathic diabetic patients.RESULTSThe PCr/Pi ratio was higher in the control subjects (3.23 ± 0.43) followed by the non-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 11 publications
3
18
0
Order By: Relevance
“…Previous studies have demonstrated that peripheral neuropathy and fear of falling are linked to changes in gait performance, 4,26,3134 and the present findings are in good agreement with these. Patients with DPN, for example, are known to adopt a conservative walking strategy, with a longer double-support phase and generally slower stride velocities compared with patients without DPN.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have demonstrated that peripheral neuropathy and fear of falling are linked to changes in gait performance, 4,26,3134 and the present findings are in good agreement with these. Patients with DPN, for example, are known to adopt a conservative walking strategy, with a longer double-support phase and generally slower stride velocities compared with patients without DPN.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies in our unit have shown foot muscle atrophy and reduced PCr levels in diabetic patients with diabetic neuropathy and increased Pi/PCr ratio at resting conditions in both non-neuropathic and neuropathic diabetic patients 18, 20, 32 . In the present study, no differences were observed at resting conditions among the four tested groups and this finding is in agreement with previous studies that included patients with PAD 1, 6 .…”
Section: Discussionmentioning
confidence: 59%
“…Phosphorus-31 MRS data was acquired at a temporal resolution of 6 sections during resting and exercise. Pi and PCr information was extracted from the data as previously published by our unit 18, 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Resting levels of high energy phosphates are reduced in the diabetic foot. 71,72 Muscle oxidative capacity is reduced by over 50% in DPN compared to DM without neuropathy. 73 The reduced mitochondrial function in DPN is related to increased inflammatory cytokines.…”
Section: The Effects Of Dpn On Skeletal Muscle Functionmentioning
confidence: 99%
“…Resting levels of high energy phosphates are reduced in the diabetic foot. 71,72 Foot muscle atrophy has been shown to be accompanied by a reduction in 31P metabolites in the foot muscles in patients with DPN compared to diabetic patients without neuropathy, and healthy controls. 52 …”
Section: Non-invasive Mri Techniques To Assess Dpn Featuresmentioning
confidence: 99%